Ascertaining species of origin from confiscated meat using DNA forensics. Issue 1 (2nd January 2019) - Ghosh, Avijit; Basu, Sambadeb; Khatri, Hiren; Chandra, Kailash; Thakur, Mukesh
Abstract: Poaching of wildlife for local consumption and commercial purposes is a major threat to the loss of the world's biodiversity which has even resulted in the extirpation of the numerous species at local or regional scale. Law enforcement agencies have been working in the implementation of the Wildlife Protection Act to combat illegal trade of wildlife for parts and products all across the world. Nevertheless, several times confiscated materials have been altered and fabricated so much that their morphological identification often got difficult. In the last few decades, DNA technology has revolutionized species identification in forensic investigations and has shown its power in the firm identification of those fabricated materials. We received a confiscated material, appeared to be chopped raw meat with no intact morphological identity. The accused was caught by the officials of the State Forest Department after he put pictures on social media depicting his involvement in cooking and eating of animal meat, suspected to be of wildlife origin. On homology search, we found a 99% identity of the confiscated material with Asian Palm Civet ( Paradoxurus hermaphroditus) and neighbour joining trees based on genetic distances clustered the query sequence with the Asian Palm Civet with 100% bootstrap support. The present study exhibits hope for ascertaining species identification from the processed meat in reliable assessment for wildlife forensics. This case study extends, the role of the authenticated references as available on the public database, highlighting the application of DNA forensics in identifying species even from the phenotypically altered materials.